Fast oscillations >40 Hz localize the epileptogenic zone: An electrical source imaging study using high-density electroencephalography. Issue 2 (February 2021) - Avigdor, Tamir; Abdallah, Chifaou; von Ellenrieder, Nicolás; Hedrich, Tanguy; Rubino, Annalisa; Lo Russo, Giorgio; Bernhardt, Boris; Nobili, Lino; Grova, Christophe; Frauscher, Birgit
Highlights: Fast oscillations >40 Hz are able to correctly localize the epileptogenic zone. HD-EEG is superior in detection and localization of fast oscillations compared to conventional EEG approaches. Presence of fast oscillations on the scalp might point to a superficial epileptic generator. Abstract: Objective: Fast Oscillations (FO) >40 Hz are a promising biomarker of the epileptogenic zone (EZ). Evidence using scalp electroencephalography (EEG) remains scarce. We assessed if electrical source imaging of FO using 256-channel high-density EEG (HD-EEG) is useful for EZ identification. Methods: We analyzed HD-EEG recordings of 10 focal drug-resistant epilepsy patients with seizure-free postsurgical outcome. We marked FO candidate events at the time of epileptic spikes and verified them by screening for an isolated peak in the time-frequency plot. We performed electrical source imaging of spikes and FO within the Maximum Entropy of the Mean framework. Source localization maps were validated against the surgical cavity. Results: We identified FO in five out of 10 patients who had a superficial or intermediate deep generator. The maximum of the FO maps was localized inside the cavity in all patients (100%). Analysis with a reduced electrode coverage using the 10–10 and 10–20 system showed a decreased localization accuracy of 60% and 40% respectively. Conclusions: FO recorded with HD-EEG localize the EZ. HD-EEG is better suited to detect and localize FO than conventional EEG approaches. Significance: This study acts as proof-of-concept that FO localization using 256-channel HD-EEG is a viable marker of the EZ.